Elementary School Teacher Mentoring Program in Designing In-Depth Learning Plans Through Integration of Learning Outcomes and Learning Objective Flow - Thesalonika, Emelda; Sihombing, Lisbet N; Sijabat, Desi; Arent, Ease (PT. Hafasy Dwi Nawasena, 2026)
This study aims to describe the process of mentoring elementary school teachers in designing in-depth learning plans through the integration of Learning Outcomes (CP) and Learning Objective Flow (ATP) and analyze its impact on improving the quality of learning plans. The background of the study is based on the finding that some teachers still experience difficulties in systematically integrating CP and ATP, resulting in lesson plans tending to be administrative in nature and less supportive of in-depth learning. The study used a descriptive qualitative approach with a mentoring-based service model implemented at SDN 095148 Pulo Siborna. Data collection techniques included observation, interviews, and documentation studies of lesson plans before and after mentoring. The mentoring process was carried out through the stages of needs identification, strengthening conceptual understanding, design practice, and reflection and evaluation. The results showed that mentoring was able to improve teachers' understanding of the integration of CP and ATP and produce more structured, contextual, and coherent lesson plans. In addition, there was a shift in teachers' mindsets from an administrative orientation to a competency-based approach and in-depth learning. Thus, teacher mentoring is an effective strategy in supporting the implementation of the Independent Curriculum in a more meaningful and sustainable manner